Effects of salt stress on plant and rhizosphere bacterial communities, interaction patterns, and functions - Fu, Maoxing; Liu, Liying; Fu, Bingzhe; Hou, Meiling; Xiao, Yanzi; Liu, Yinghao; Sa, Duowen; Lu, Qiang (Frontiers in Plant Science, 2025)
Salt stress directly affects plant growth and has attention due to Na + 's potential to enhance the adaptability of certain plants to salt stress. However, interactions between Na + , plant and rhizosphere bacterial communities remain unclear, impeding the understanding of how Na + enhances plant adaptability to salt stress. This study aims to uncover the mechanisms by which Na + promotes alfalfa's adaptation to salt stress by enhancing rhizosphere bacterial communities. Data show significant differences in the metabolism and community composition of plant and rhizosphere bacteria. Na + addition not only directly promotes rhizosphere bacterial growth, but also induces changes in plant bacterial community succession, increasing the abundance of bacterial communities associated with alfalfa's resistance to salt stress. The chemical characteristics of alfalfa are significantly correlated with the composition and network complexity of plant and rhizosphere bacterial communities. This relationship further influences alfalfa's adaptability to salt stress. In summary, this study emphasizes the importance of Na + interactions with plant and rhizosphere bacterial communities in alfalfa's adaptation to salt stress. It provides new insights into enhancing crop resilience against salt stress in intensive agricultural ecosystems, aiming to improve crop production and ecosystem services.